Lack of Efficacy of Low‐Dose Cyclobenzaprine on Electromyographic Activity Related to Sleep Bruxism: A Randomized Crossover Double‐Blind Placebo‐Controlled Clinical Trial - Matheus Herreira‐Ferreira; Cibele Dal Fabbro; Gilles J. Lavigne; Juliana Stuginski‐Barbosa; Peter Svensson; Paulo César Rodrigues Conti; Leonardo Rigoldi Bonjardim (Journal of Sleep Research, 2026)
ABSTRACT Sleep bruxism (SB) is a motor activity characterized by repetitive masticatory muscle contractions during sleep, commonly associated with tooth damage and jaw pain or headache. Pharmacological management strategies targeting its central nervous system‐related mechanisms remain limited. This study aimed to evaluate whether a low dose of a central muscle relaxant, cyclobenzaprine, reduces SB‐related muscle activity, maximum voluntary bite force and self‐reported bruxism awareness. A randomized, double‐blind, placebo‐controlled, crossover clinical trial was conducted. Twenty participants underwent baseline SB motor activity recordings followed by two intervention phases consisting of 5 mg of cyclobenzaprine or placebo for three consecutive nights. Masticatory muscle activity during sleep was quantified using portable surface electromyography. Maximum voluntary bite force was measured using a bite force‐recording device. Self‐reported outcomes related to SB and secondary effects (e.g., dry mouth) were collected each morning. Comparison of cyclobenzaprine to placebo and baseline nights failed to show a difference in mean frequency of masticatory muscle activity during sleep and maximum voluntary bite force. No self‐reported differences were observed for SB awareness. Few secondary effects were identified between cyclobenzaprine use and placebo; a significant increase in perception of tolerable dry mouth upon awakening ( p = 0.034) and a marginally statistically significant reduction in the perceived leg movements during sleep ( p = 0.046). In conclusion, low‐dose cyclobenzaprine was not effective in modifying SB–related muscle activity or masticatory muscle force, suggesting limited clinical utility for SB. Future studies using higher doses of cyclobenzaprine are warranted before ruling out its clinical utility, within a safety profile.